Disturbance of Water Balance in The Body and its Effect on Brain Tissue - Ҳазратов Еъзоз Эркинович (Scientific Trends, 2025)
Violation of water balance in the body is one of the most important problems affecting the physiological state of a person. This condition can lead to a variety of diseases, including nervous system disorders and brain damage. This article discusses the mechanisms of water imbalance, its impact on brain activity, as well as existing methods of correcting this problem. The article is based on a systematic analysis of modern scientific data and statistical studies confirming the importance of water balance for the normal functioning of the central nervous system.
Keywords: Water balance, hypohydration, hyperhydration, brain, neuropsychological disorders, hyponatremia.